2015
DOI: 10.1016/j.ymgmr.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-1 contributes significantly to the degradation of neuronal B-series gangliosides but not to the bypass of the catabolic block in Tay–Sachs mouse models

Abstract: Tay–Sachs disease is a severe lysosomal storage disorder caused by mutations in the HEXA gene coding for α subunit of lysosomal β-Hexosaminidase A enzyme, which converts GM2 to GM3 ganglioside. HexA−/− mice, depleted of the β-Hexosaminidase A iso-enzyme, remain asymptomatic up to 1 year of age because of a metabolic bypass by neuraminidase(s). These enzymes remove a sialic acid residue converting GM2 to GA2, which is further degraded by the still intact β-Hexosaminidase B iso-enzyme into lactosylceramide. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(47 reference statements)
2
8
0
Order By: Relevance
“…Further studies, however, demonstrated that NEU1 has negligible activity against ganglioside substrates, in contrast with NEU3 and NEU4 [ 29 ]. In agreement with this, Hexa −/- CathA S190A-neo mice with secondary 90% deficiency of NEU1 in the tissues do not show an increase in brain GM2 levels as compared with Hexa −/− mice [ 78 ]. Li 2001 et al .…”
Section: Catabolism Of Brain Gangliosides: Neu1 Neu3 or Neu4?supporting
confidence: 59%
“…Further studies, however, demonstrated that NEU1 has negligible activity against ganglioside substrates, in contrast with NEU3 and NEU4 [ 29 ]. In agreement with this, Hexa −/- CathA S190A-neo mice with secondary 90% deficiency of NEU1 in the tissues do not show an increase in brain GM2 levels as compared with Hexa −/− mice [ 78 ]. Li 2001 et al .…”
Section: Catabolism Of Brain Gangliosides: Neu1 Neu3 or Neu4?supporting
confidence: 59%
“…Interestingly, the increased presence of asialo-G M1 (G A1 ) is compatible with an alternative degradation pathway for G M1 and G A1 . The presence of a higher amount of G A1 indicates that murine enzymes exhibit a different affinity towards degradation products, which is also described in another model for G M1 -gangliosidosis [22] and for murine neuraminidases in a model for Morbus Tay-Sachs [44].…”
Section: Discussionsupporting
confidence: 57%
“…Surfaces of mammalian neurons are enriched in GGs of the a-and b-ganglio-series (e.g., GM1a, GD1a, GD1b, GT1a, GT1b, and polysialo-GGs), carrying up to six sialic acid residues [9]. Desialylation of complex polysialo-GGs to eventually generate GG GM1 is catabolized mainly by three membrane-bound sialidases with overlapping substrate specificities and differing subcellular location, neuraminidase NEU1, NEU3, and NEU4 [42][43][44]. The plasma membrane-bound NEU3 is the key enzyme for degradation of polysialo-GGs and is involved in many surface phenomena, whereas NEU1 is the major sialidase of endosomes and lysosomes to hydrolyze polysialo-GGs to generate GM1 [45].…”
Section: Lysosomal Catabolism Of Ggsmentioning
confidence: 99%